taVNS as a potential countermeasure for neurocognitive decline in microgravity - Fricke, L.; Wienke, C.; Zaehle, T. (Frontiers in Neuroscience, 2025)
Exposure to microgravity induces significant physiological, cognitive, and psychomotor changes in the human body. While countermeasures such as resistance exercise and cardiovascular conditioning have been developed to address musculoskeletal and circulatory issues, there remains a critical gap in mitigating neurophysiological and cognitive deficits caused by microgravity. Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive neuromodulation technique that promises to enhance psychomotor function, and cognitive performance in microgravity as well as on Earth. This article examines the challenges of spaceflight, particularly cognitive impairments and related psychomotor dysfunction, and explores the potential application of taVNS in space. The neurophysiological mechanisms underlying microgravity-related decline and the proposed mechanism of action of taVNS are discussed, focusing on its effects on neuroplasticity, autonomic regulation, and sensorimotor integration. taVNS emerges as a promising countermeasure to mitigate neuropsychological impairments associated with exposure to microgravity.